Innovation and production clusters in Europe - Rosina Moreno; Raffaele Paci; Stefano Usai (European Regional Science Association (ERSA), 2004)
This paper investigates on the presence of innovation and production clusters in Europe. The analysis is based on an original statistical databank set up by CRENoS on regional patenting at the European Patent Office spanning from 1978 to 1997 and classified by ISIC sectors (3 digit) and on the Cambridge Econometrics database on production activity. We consider 138 regions of 17 countries in Europe, the 15 members of the European Union plus Switzerland and Norway. Firstly, an analysis of the spatial distribution of innovation and production activities in Europe is performed. Some global and local indicators for spatial association are presented, summarising the presence of a general dependence process in the distribution of the phenomena under examination. The analysis is implemented for different manufacturing macro-sectors to assess for the presence of significant differences in the their spatial features. Moreover, the extent and strength of spatial externalities are evaluated for three different periods: 1981-83, 1988-90 and 1995-97. Secondly, the spatial mapping of innovation is compared to the distribution of productive activity. Keywords: Innovation activity, Production specialisation, Spatial analysis, European regions.
Keywords: 330; Innovation activity; Production specialisation; Spatial analysis; European regions